Heritage based curriculum: Teacher preparedness and implementation- a case for Zimbabwe - Chitamba, Norman; Chitamba, Anos (Edelweiss Applied Science and Technology, 2025)
On May 7, 2024, the Ministry of Primary and Secondary Education launched the Heritage-Based Curriculum (HBC) [1]. The primary objective of HBC is to prepare students for active citizenship and instill in them a deep appreciation for the Zimbabwean philosophical principles of unhu/ubuntu/vumunhu. Furthermore, HBC emphasizes the preservation and transmission of cultural, historical, and traditional knowledge [2]. Teachers play a crucial role in the implementation of this curriculum, as they are often referred to as curriculum implementers [3]. This paper is guided by four key questions: (1) What is your understanding of HBC? (2) How do you perceive teacher preparedness? (3) In what ways can teachers be supported to ensure effective curriculum implementation? (4) What challenges do teachers encounter during the implementation of HBC? This study focuses on teacher preparedness for HBC implementation, specifically in the Gutu District of Masvingo Province, Zimbabwe. It is grounded in curriculum theory, which provides a framework for various curriculum-related tasks, including design, development, implementation, and supervision. The methodology employed purposive sampling, along with focus groups and interviews with secondary school teachers in the Gutu district. Research findings indicated that HBC had not yet been introduced in schools, teachers had not undergone in-service training, and they were unprepared for the new curriculum. The timing of the May 7, 2024, launch, combined with the lack of teacher engagement, can be likened to the Igbo proverb about “going for a cry without eyes.” This study advocates for a grassroots approach to curriculum implementation, which recognizes the essential role of teachers in this process [4]. Additionally, the study recommends comprehensive in-service training for teachers prior to the introduction of HBC to ensure effective implementation. Engaging parents as stakeholders can further enhance deep learning by promoting inquiry-based approaches [5]. Ultimately, the study concludes that HBC holds significant potential to cultivate patriotism and reinforce the Zimbabwean philosophy of ubuntu/unhu/vumunhu, thereby contributing to the decolonization of the curriculum.